Isolation of Pseudomonas pickettii strains that degrade 2,4,6-trichlorophenol and their dechlorination of chlorophenols. - Kiyohara, H (1992)
Three strains of Pseudomonas pickettii that can grow with 2,4,6-trichlorophenol (2,4,6-TCP) as the sole source of carbon and energy were isolated from different mixed cultures of soil bacterial populations that had been acclimatized to 2,4,6-TCP. These strains released 3 mol of chloride ion from 1 mol of 2,4,6-TCP during the complete degradation of the TCP. Of these strains, P. pickettii DTP0602 in high-cell-density suspension cultures dechlorinated various chlorophenols (CPs). Cells that were preincubated with 2,4,6-TCP converted isomers of 4-CP to the corresponding chloro-p-hydroquinones, but those preincubated with 4-CP converted CPs lacking a chlorine atom(s) at the o position to isomers of chlorocatechol. The ability of DTP0602 to dechlorinate 2,4,6-TCP was induced by 2,6-dichlorophenol, 2,3,6- and 2,4,6-TCP, and 2,3,4,6-tetrachlorophenol and was repressed in the presence of succinate or glucose.